2006
DOI: 10.1108/03321640610666880
|View full text |Cite
|
Sign up to set email alerts
|

Computation of eddy current losses in the mounting rail of a magnetically levitated conveyor vehicle

Abstract: Purpose -The paper proposes presenting a transient 3D-FE computation approach of the eddy current losses in the rail and the flux concentrating pieces of a magnetically levitated conveyor vehicle. Design/methodology/approach -The calculation process is started with a coarse mesh in order to reduce computation time without losing accuracy. Then mesh refinement iterations are performed, based on the estimation of the discretisation error. The results of the post processing are the levitation force, the braking f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…But the more relevant losses are the iron losses. In [5] it is shown that the eddy current losses amount to 200 W at 10 m/s for all four magnets.…”
Section: ) Levitation Lossesmentioning
confidence: 98%
See 2 more Smart Citations
“…But the more relevant losses are the iron losses. In [5] it is shown that the eddy current losses amount to 200 W at 10 m/s for all four magnets.…”
Section: ) Levitation Lossesmentioning
confidence: 98%
“…2) Propulsion Losses: The iron losses of the linear drives will increase from zero at standstill to 300 W at 10 m/s [5]. To compensate the overall iron losses of the system at this speed the propulsion has to produce a force of This means that the copper losses are only 20 W at constant speed.…”
Section: ) Levitation Lossesmentioning
confidence: 98%
See 1 more Smart Citation
“…Finite‐element analysis software is suitable to analyze electromagnetic characteristics (Leßmann and Hameyer, 2006). Finite‐element method (FEM) based software ANSOFT is used to analyze the proposed BSRM in several static states, assuming motor axis symmetry.…”
Section: Electromagnetic Analysis Of the Proposed Bsrmmentioning
confidence: 99%
“…The lower is the friction between the chain and the beam, the lower is the power consumption and the surface wear. The magnetic levitation technology can be utilized to reduce friction using properly designed coils (Leßmann and Hameyer, 2006;Hong and Kim, 2008) or permanent magnets (PM) (Moser et al, 2006;Ravaud et al, 2009a, b;Long et al, 2011;Bachovchin et al, 2013). Passive repulsive bearing using PM have been extensively studied and can be used in motors, turbines, flywheels, etc.…”
Section: Introductionmentioning
confidence: 99%